FAKTOR-FAKTOR YANG MEMPENGARUHI WORD OF MOUTH INTENTIONS PELANGGAN PADA RESTORAN INDONESIA ETHNIC DI SURABAYA - Rendy Wahyu Saputra; Dudi Anandya; Indarini Indarini (Perpustakaan Universitas Surabaya, 2018)
The purpose of the study was to find out influence food quality, personal interaction quality, physical environment quality, perceived value, and relationship quality (satisfaction, trust, and commitment) would affect word of mouth intentions of the customers of the ethnic Indonesian restaurant industry in Surabaya. The research was analyzed using Structural Equation Modelling (SEM) and the statistical package for Social Sciences (SPSS) version 18 and Lisrel 8.70.200respondents were chosen from the customers visiting and recomendating on of the ten ethnic Indonesian restaurant in Surabaya within the last 6 months. The result of the research found that food quality, personal interaction quality, physical environment quality, and perceived value have positive and significant influence on satisfaction. The satisfaction perceived by the customer has positive and significant influence on trust, commitment, and word of mouth. Trust and commitment have no significant effect on word of mouth intentions. The customers satisfied of the whole ethnic Indonesian restaurant service in Surabaya will be loyal to the restaurant, suck as having positive word of mouth to other people around them.